GROWTH AND YIELD OF SOYBEAN WITH PENERGETIC APPLICATION - Aparecido de Souza, Adriano; Zanuto de Almeida, Fabio; Alberton, Odair (Scientia Agraria, 2017)
The soybean (Glycine max L.) plant is economically important for the food and animal feed industries due to its nutritional qualities. Soybean crops are highly productive and responsive to new technologies. The aim of this study was to assess the effect of Penergetic-P and Penergetic-K on the dry weight of shoot (DWS), dry weight of root (DWR), total dry weight (DWT), dry weight of nodules (DWN), number of nodules per plant (NNP), level of N in the shoot (NS), chlorophyll index, plant height and soybean yield. The experiment was conducted in a randomized block design with three replications. The means were compared by ANOVA and Duncan test (p ≤ 0.05). Differences among treatments for NNP were not significantly evident, but observed for DWN. The application of Penergetic-K in soil increased significantly the DWN in comparison with the application of only NPK and micronutrients. The DWR, DWS, DWT and the DWS/DWR ratio didn’t differ significantly among the treatments as well as the chlorophyll index and NS. The grain yield was significantly lower with the addition of NPK + micronutrients and significantly higher with the addition of Penergetic-K. The Penergetic-K promoted an increased soybean yield, up to 20% compared to the treatment with only NPK + micronutrients. It was concluded that the use of Penergetic benefits the soybean production and the soil quality.